Environmental Management Challenges of Emerging Industrial Firms: Evidence from Addis Ababa City, Ethiopia - Urkato, Samuel; Shin, Hio-Jung (American Journal of Trade and Policy, 2015)
In developing economies like Ethiopia, emerging industries are mostly subject to state protection, as a prominent rationale articulated by Hamilton (1791). However, they are less responsive to environmental health degradation caused by their effluent. In this paper, Akaki River pollution in Addis Ababa city is thought-out to understand how those industries aligning the river bank are polluting the environment and how local policy is responding to regulate it. By using secondary information, focus group discussion and key informant interview, this study describes that Ethiopian environmental policy, which addresses state and market approaches, is silent to protect the pollution. However, the societies in the catchment areas, whom lack proper property right of the river, are seriously vulnerable to family health since they use the polluted river water for smallholder farming, drinking, and other domestic activities. Moreover, the weak performance of this policy is a burden for other sectoral policies such as health and agriculture. Empirical studies for river pollution impact are further needed.
Keywords: Emerging industry; environmental resource; policy; Addis Ababa